Sex Differences in the Sustained Effects of Ketamine on Resilience to Chronic Stress - Okine, Tracy; Shepard, Ryan; Lemanski, Elise; Coutellier, Laurence (Frontiers in Behavioral Neuroscience, 2020)
Exposure to stress is recognized to be a triggering factor to several mood disorders, including depression and anxiety. There is very little understanding of why female subjects have a significantly higher risk for these conditions than males. Recent findings in male rodents indicated that prophylactic ketamine can prevent the development of a stress-induced depressive-like phenotype, providing a pharmacological tool to study the mechanisms underlying stress resilience. Unfortunately, none of these studies incorporated female subjects, nor did they provide a mechanistic understanding for the effects of ketamine on stress resilience. Our previous work identified the prefrontal glutamatergic and parvalbumin (PV) systems as potential molecular mechanisms underlying sex differences in susceptibility to stress-induced emotional deregulations. To further address this point, we treated male and female mice with a single dose of ketamine prior to exposure to a chronic stress paradigm to determine whether stress-resilience induced by a pre-exposure to ketamine is similar in males and females, and whether modulation of the prefrontal glutamatergic and PV systems by ketamine is associated with these behavioral effects. Ketamine prevented chronic stress-induced changes in behaviors in males, which was associated with reduction in expression of PV and of the NMDA receptor NR1 subunit. Ketamine did not protect females against the effects of chronic stress and did not change significantly prefrontal genes expression. Our data highlight fundamental sex differences in the sustained effects of ketamine. They also further implicate prefrontal glutamatergic transmission and PV in resilience to chronic stress.